PERLINDUNGAN HUKUM DALAM PENYELENGGARAAN IBADAH UMROH DAN HAJI: ANALISIS PENCEGAHAN KEGAGALAN KEBERANGKATAN PERJALANAN IBADAH - Imam Toyib Abdulah; Arista Candra Irawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article examines the effectiveness of legal protection for pilgrims in the implementation of umrah and hajj services by travel agencies in Indonesia, particularly in cases of departure failure. The study applies both normative and empirical juridical approaches by analyzing consumer protection regulations and the actual practices of agencies that failed to deliver services. Findings reveal a significant gap between existing legal norms and their implementation in the field. The causes of departure failure include weak internal management, unsound financing schemes, lack of government oversight, and low public legal literacy. Legal remedies pursued by victims include civil, criminal, and non-litigation pathways; however, these measures remain suboptimal due to limited access and ineffective restitution mechanisms. Law enforcement tends to focus on administrative sanctions without guaranteeing the recovery of pilgrims’ losses. This article recommends regulatory reform, inter-agency supervision strengthening, and the implementation of standardized contracts and escrow accounts to ensure substantive protection of pilgrims’ rights.